Изображение римского шлема на надгробной стеле Басилида из некрополя Пантикапея: The Image of a Roman Helmet from the Grave Stela of Basilides from the Necropolis of Panticapaeum - Горончаровский, Владимир (Acta Archaeologica Lodziensia, 2019)
Study of written, pictorial and archaeological sources show that the influence of military machine of the Roman Empire on the Bosporan Kingdom was limited. Its main effect was on the organizational structure and tactics. Some examples of Roman military equipment could have found their way to the Bosporus during preparations for joint military actions with the Roman army. Maybe local natives, serving in Roman auxiliary units, played some role in this respect also.